2017
DOI: 10.17221/617/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inoculation with arbuscular mycorrhizal fungus Rhizophagus irregularis on cytokinin content in a highly mycotrophic Medicago lupulina line under low phosphorus level in the soil

Abstract: Arbuscular mycorrhizae (AM) is a mutualistic nonspecific symbiosis formed by most land plant families (92%) with fungi represented by the Glomeromycota phylum. This type of symbiosis is The study is focused on the elucidation of the role of cytokinins (CKs, zeatin and zeatin riboside) in the development of effective arbuscular mycorrhiza (AM) symbiosis with Medicago lupulina. An important mechanism involved in the regulation of host plant growth is supposed to be linked to the modulation of plant hormone bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(40 reference statements)
3
6
0
1
Order By: Relevance
“…For instance, mycorrhizal colonization did not appear to alter gene expression in the CK signaling of the legume species Medicago truncatula (Laffont et al, 2015). Yet, recent studies employing powerful biochemical tools (Adolfsson et al, 2017; Schmidt et al, 2017; Yurkov et al, 2017) confirmed what earlier studies had documented (e.g., Allen et al, 1980; Shaul-Keinan et al, 2002), i.e., that mycorrhizal (myc + ) plants exhibit altered CK levels compared to non-mycorrhizal (myc - ) plants. The intensity of these mycorrhizal effects on CK accumulation in plants depends on the fungal species, P availability in soil, as well as on plant tissue and development stage.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For instance, mycorrhizal colonization did not appear to alter gene expression in the CK signaling of the legume species Medicago truncatula (Laffont et al, 2015). Yet, recent studies employing powerful biochemical tools (Adolfsson et al, 2017; Schmidt et al, 2017; Yurkov et al, 2017) confirmed what earlier studies had documented (e.g., Allen et al, 1980; Shaul-Keinan et al, 2002), i.e., that mycorrhizal (myc + ) plants exhibit altered CK levels compared to non-mycorrhizal (myc - ) plants. The intensity of these mycorrhizal effects on CK accumulation in plants depends on the fungal species, P availability in soil, as well as on plant tissue and development stage.…”
Section: Introductionsupporting
confidence: 72%
“…Among the many studies performed, two are of interest as the CK content was measured at different stages of AM development. While van Rhijn et al (1997) measured CK in myc + alfalfa plants at 14, 16, and 18 DAI, Yurkov et al (2017) determined CK content in Medicago lupulina at 1, 14, 21, 35, and 50 DAI. In both studies, CK levels were estimated by immunoassay, and thus their results are difficult to compare to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Such a decrement might be caused by the necessity of energy and metabolites supporting developmental processes for the host plant. According to our earlier data, M. lupulina's SH stage was characterized by a maximum increase in symbiotrophic P i uptake, both in leaves and roots [41]. Further plant development from SH to SBI was accompanied by the sharp increase in symbiotic efficiency in the weight of both aerial parts and roots.…”
Section: Discussionmentioning
confidence: 77%
“…The possibility of active metabolic processes in symbiotic mycelium might be realized by diverse types of AM-for instance, the Paris type [45]. A significant role of mycelium in the effective AM symbiosis in the latter stages was shown for symbiosis of M. lupulina with R. irregularis [41]. The expression of sucrose fungal transporter gene MST2 (in M. truncatula + Glomus sp.…”
Section: Discussionmentioning
confidence: 99%
“…В связи с этим мы будем анализировать транспортеры видов растений, образующих АМ, с учетом их гомологии с транспортерами A. thaliana. К видам-микоризообразователям относится такое распространенное модельное растение, как люцерна усеченная (Medicago truncatula); также новым объектом для исследований АМ может стать селектированная авторами обзора сильно микотрофная люцерна хмелевидная (Medicago lupulina) [74]. Анализ литературных данных дает возможность заключить, что многие растительные транспортеры сахаров не обладают специфичностью для АМ, кроме недавно открытых двунаправленных унипортеров семейства SWEET [22,61].…”
Section: растительные транспортеры сахаров при развитии ам-симбиозаunclassified